Language without code: intentionally unusable, uncomputable, or conceptual programming languages - Temkin, Daniel (2017)
The esoteric class of programming languages, commonly called esolangs, have long challenged the norms of programming practice and computational culture. Esolangs are a practice of hacker/hobbyists, who don’t primarily think of their work as art. Most esolangs are experiential works; we understand the languages by writing code in them. Through this action, the logic of the language becomes clear. However, a smaller subset of esolangs make their point not through actively writing code, but instead by simply contemplating their rules. We can think of these esolangs as conceptual rather than experiential. Some are designed in such a way that they don’t allow any code to be written for them at all. By stepping away from usability, the conceptual esolangs offer the most direct challenge to the definition of programming language, a commonly used term which is surprisingly unspecific, and usually understood through utility, despite the fact that programming languages predate digital computers. This paper delves into the conceptual esolangs and looks at their challenge to the idea of programming languages.